Disruption of the biological clock: chronotypes and social jet lag in high school students - Chura-Quispe, Gilber; Gutierrez Flor, Karla Antonella; Valencia Valencia, Julio Berne; Alca Gómez, Javier; Quispe Mello, Enrique José; Alca Gómez, Americo (International Journal of Evaluation and Research in Education (IJERE), 2025)
Adolescent students generally experience variations in sleep that can lead to discrepancies between the biological rhythms of their daily lives and social demands such as school schedules, affecting not only their physical and mental health but also their learning process. Therefore, this study aims to investigate the relationship between chronotype types and the prevalence or absence of social jet lag among adolescents aged 13 to 17 years. A quantitative approach was adopted, utilizing a cross-sectional and descriptive-correlational design, with a participation of 524 secondary school students and a non-probabilistic sample of 267, to whom two questionnaires were administered. The findings indicated the absence of a significant correlation between chronotypes and social jet lag (p=0.916, VCramer=0.026). Moreover, the predominant chronotype was intermediate (81.27%), and 83.15% were likely experiencing jet lag. Additionally, 60% of adolescents aged 15 to 16 years have an evening chronotype, and 35.59% of those suffering from jet lag are 16 years old. In conclusion, although the correlation between chronotypes and jet lag was not demonstrated, the issue of biological clock disorders is present among school students, particularly among those aged 16.